Rancang Bangun Sistem Pelipat Pakaian Menggunakan Sensor Load Cell dan Sensor Ultrasonik Berbasis Arduino Mega2560 - Jihan Latifah Hanum; Nini Firmawati (Universitas Andalas, 2025)
A clothes folding tool has been made using 4 load cell sensors and a clothes container using an ultrasonic sensor based on the Arduino Mega2560. Load cell sensor to detect mass on the folding board, if the mass is small equal to 375g, then the MG996R servo motor is active, if the mass is greater than 375g, then the servo motor is not active, the LCD screen displays excess mass. The HC-SR04 ultrasonic sensor detects the distance between clothes and clothes folders. If the detected distance is 2 cm, the buzzer sounds more than once. The buzzer also sounds once indicating the folding process is complete. The characteristics of load cell sensors 1, 2, 3, and 4 have linear correlation coefficients of 0.9985, 0.9985, 0.9968, and 0.998 respectively. The characteristics of the ultrasonic sensor have a linear correlation coefficient of 1. The average folding time is obtained from the folding time using a folding tool and the folding time manually 3 times for each garment. The average manual folding of shirt A, shirt B, trousers A, and trousers B was 9.07s, 15.34s, 9.68s, and 10s respectively, while using a folding tool was 5, respectively. 47s, 5.49s, 5.44s, and 5.47s. Testing variations in clothing mass with clothing folding time, it was found that variations in clothing mass had no effect on the length of time folding clothing